The effect of dihydroartemisinin-piperaquine on smooth muscle contractility and other activities in animal models. - Tologbonse, Adedayo A.; Onwuka, Ngozi A.; Michael, Archibong A.; Udoh, Anwangabasi E.; Smart, Archibong A.; Olorunsola, Emmanuel O.; Essien , Grace E.; Mbagwu, Herbert O. C. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2025)
Background: Malaria remains a major health challenge in sub-Saharan Africa. While dihydroartemisinin (DHA) and its combinations combat resistant malaria, they can cause side effects like nausea, vomiting, and dizziness. This study investigated the effects of DHA and DHA/piperaquine on acetylcholine-induced ileum smooth muscle contraction using in vitro and in vivo models Methods: In-vitro experiments utilized ileum strips from adult Wistar rats (180–200 g) mounted on organ baths, with responses to acetylcholine, potassium chloride, and barium chloride serving as controls. For in vivo experiments, 60 adult albino mice (20–25 g) were divided into test and control groups (n=5). Test groups were infected with Plasmodium berghei and treated with DHA-piperaquine (3.0, 6.0, 9.0 mg/kg) or pure DHA (6.0, 9.0 mg/kg) orally, twice daily for five days. Control groups included non-infected/treated, non-infected/non-treated, and infected/non-treated subgroups, with untreated mice receiving 0.5 mL of distilled water. All animals were fasted for 24 hours before being sacrificed on day seven to harvest ileum tissues for histopathological analysis. Results: Pure DHA and the DHA/P-Alaxin combination did not exhibit agonist effects on ileum smooth muscles but dose-dependently inhibited contractions induced by acetylcholine, potassium chloride, and barium chloride. DHA showed a significant mean inhibitory response (40.5%) on acetylcholine-induced contractions compared to atropine (77.0%) (P < 0.05). Histopathological analysis revealed tissue-friendly effects at moderate therapeutic doses, though mild to moderate cellular changes were observed at 9 mg/kg. Conclusion: Dihydroartemisinin significantly and dose-dependently inhibited acetylcholine-induced contractions. It demonstrated a safe cellular profile on ileum smooth muscle at therapeutic doses.